The effect of orientation of the lateral methyl substituent on the mesophase behaviour of 4-alkoxyphenylazo aryl benzoates. Issue 12 (25th September 2016) - Naoum, Magdi M.; Fahmi, Abdelgawad A.; Abaza, Amira H.; Saad, Gamal R.
ABSTRACT: Two homologous series of 4-alkoxyphenylazo 4ʹ-(2ʺ- (and 3ʺ-) methyl-) 4ʹ-substituted benzoates (II n a–f andIII n a–f, six series each) were prepared and investigated. Within each series, the length of the terminal alkoxy group varies among 6, 8, 10 and 12 carbons, while the other terminal substituent, X, is a polar group that alternatively changes between the electron-donating CH3 O, CH3, and the electron-withdrawing Br, NO2 and CN groups, in addition to the un-substituted analogue, X = H, aiming to investigate the effect of the different orientations of the methyl groups substituted on the central benzene ring, on the mesophase behaviour. The mesomorphic properties were discussed in terms of steric and polarisability effects. The mesophase stability was correlated with the polarisability anisotropy of bonds to the terminal substituent X. Comparative studies were made between the prepared isomers with each other and with the previously investigated laterally neat analogues 4-(4ʹ-alkoxyphenylazo) phenyl 4ʺ-substituted benzoates (I n a–f ). GRAPHICAL ABSTRACT: